GroupStruct: An R Package for Allometric Size Correction - Chan, Kin Onn; Grismer, L. Lee (Zootaxa, 2022)
The efficacy of an allometric growth model to correct for ontogenetic body size variation has been known for decades, yet this method remains relatively obscure and rarely applied. We optimize the implementation of this method through a newly developed and easy-to-use R package GroupStruct and further extend its application from intraspecific to interspecific datasets. Using empirical examples, we show that different size correction methods (i.e., ratios, residuals, and allometry) can result in vastly different conclusions. Our results demonstrate that choosing the appropriate size correction method is crucial as it can have significant impacts on downstream analyses and has the potential to alter biological interpretations.